(untitled) (Research, Society and Development, 2021)
The treatment of hemophilia carried out at home presents the need to control infusions, made through the registration in a printed diary. Objective: To describe the process of developing a follow up mobile application for patients with hemophilia. Methodology: The development of the application took place in two stages, the first corresponding to the analysis of the demand of hemophiliacs and the second it is about design and development, created from the same code, using a hybrid technology. Results: HemoCheck is available on Android and iOS platforms; offer screens that provide guidance on the disease, for recording the history of infusions and complications; to the user’s profile and a button to contact the registered blood center. Conclusion: The study fulfilled the proposed objective and given the results found, it is recommended that the quality analysis of HemoCheck and its impact on patients’ lives be carried out through other inquiries.